Exploring Dynamic Mentoring Models in India (Springer International Publishing, 2018)
'Although mentoring is a universal relationship, we know little about cultural variations in its processes and outcomes. Addressing this gap, this volume offers important and needed insights on mentoring in India and will be a key resource for scholars and practitioners.' -Belle Rose Ragins, Professor, University of Wisconsin-Milwaukee, USA and Editor of Academy of Management Review This edited collection explores the variations of mentoring in India in comparison to western models, providing rich contextual interpretation and paving the way for a greater understanding of mentoring as a phenomenon. With India having the world's largest youth population, its longstanding mentoring tradition is increasingly being replaced by emerging mentoring models in which younger generations are constantly exposed to both Indian and western influences. Paying particular attention to formal and informal mentoring models, the contributions cover the corporate sector, higher education, the developmental sector and venture capitalist-enabled entrepreneurial mentoring. Offering a uniquely non-western perspective, this innovative study also showcases both mentor and protégé perceptions of mentoring, and will be of great appeal to both practitioners and scholars of leadership.